Improving language acquistion and motivation in learning English as a second language through journal writing / Mohd Zulfahmi Ab Salam - Ab Salam, Mohd Zulfahmi (2010)
Education in Malaysia has been exam-oriented for so long. Therefore, students are rarely exposed to the “creative” and “intuitive” style of writing. They are taught to be adapted to the more formulaic style of writing. As a result, most view the process of writing as boring and hard and thus they are reluctant to learn and improve. Journal writing has been proven by previous studies to be effective in enhancing students’ language acquisition and motivation to learn. Therefore, the aim of this study is to examine the effectiveness of journal writing in language development, especially English. This study examined how journal writing can be used a tool to improve second language acquisition and enhance the motivation to improve in language skills – preferably writing. The respondents were ten Form 2 students. Through out the research period, the respondents were required to answer surveys at the beginning and at the end of the research, write variety types of journals (personal, literary and dialogue) and those journals were assessed using a rubric adopted from a previous study of the same area. Modeling was also applied during the process of writing.